Batasan Tanggung Jawab Hukum Pengelola Jasa Parkir: Studi Putusan Mahkamah Agung Nomor 2157 K/Pdt/2010 - Rahmad Tullah; Purwanto Purwanto; Setiyo Utomo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research is directed to answer two main problems: the form of liability imposed on parking service providers toward consumers, and how the Supreme Court decision reflects (or diverges from) legal justice and proportionality. The study aims to examine the legal liability approach adopted in the Supreme Court Decision Number 2157/K/Pdt/2010 and to formulate an ideal concept of a fair and proportional limitation of liability for parking service operators. In the aforementioned decision, the Supreme Court held the parking operator liable for the loss of a consumer’s vehicle, even though a disclaimer clause had been clearly printed on the parking ticket. This ruling raised controversy, as it seemed to overlook the fact that the operator had fulfilled their duties to a reasonable and professional standard. The substance of parking as an object of regional tax was disregarded in the judicial consideration, which focused solely on consumer protection law. This has led to an interpretation that imposes an almost unlimited liability on the service provider. This study employs doctrinal legal research, supported by conceptual approaches in parking regulation and legal case analysis. The method used is normative legal research (doctrinal) with statutory, conceptual (regarding lease and deposit agreements), and judicial approaches. The findings indicate that parking service providers should not be subjected to absolute liability. Instead, the assessment of liability must take into account the principles of justice, proportionality, and contributory negligence. Hence, there is a need for a clear formulation of liability limitations that not only safeguard consumer rights but also consider the reasonable obligations of business actors, particularly within the context of regional tax regulations related to parking.